Modifications in magnetic anisotropy of M-type strontium hexaferrite crystals by swift heavy ion irradiation - Kaur, Balwinder; Bhat, Monita; Licci, F.; Kumar, Ravi; Kulkarni, S. D.; Joy, Pattayil Alias; Bamzai, K. K.; Kotru, P. N. (Journal of Magnetism and Magnetic Materials, 2006)
Using vibrating sample magnetometery (VSM) 50 MeV Li(3+) ion irradiation effects on magnetic properties of single crystals of SrGa(x)In(y)Fe(12-(x+y))O(19) (where x = 0, 5, 7, 9; y = 0, 0.8, 1.3, 1.0), are reported. The substitution of Ga and In in strontium hexaferrite crystals decreases the value of magnetization sharply, which is attributed to shifting of collinear magnetic order to a non-collinear one. Reduction of magnetization is also explained to be as a result of the occupation of the crystallographic sites of Fe(3+) by Ga(3+) and In(3+). The Li(3+) ion irradiation decreases the value of magnetization, irrespective of whether the crystals are Ga-In substituted or unsubstituted crystals of SrFe(12)O(19). The result is interpreted in terms of the occurrence of a paramagnetic doublet in crystals replacing magnetic sextuplet as a result of irradiation. Substitution of Ga-In in Strontium hexaferrite decreases the value of anisotropy constant. Irradiation with Li(3+) ions increases the values of anisotropy field for both substituted as well as unsubstituted crystals. Substitution with Ga-In also decreases the Curie temperature (T(c)) but the irradiation with Li(3+) ions does not affect the curie temperature of either Ga-In substituted or pure SrFe(12)O(19) crystals. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: anisotropy field; Curie temperature; irradiation; Magnetic anisotropy; Magnetization